1988
DOI: 10.1093/nar/16.23.11303
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the herpes thymidine kinase: identification and comparison of the equine herpesvirus 1 thymidine kinase gene reveals similarity to a cell-encoded thymidylate kinase

Abstract: We have identified the equine herpesvirus 1 (EHV-1) thymidine kinase gene (TK) by DNA-mediated transformation and by DNA sequencing. Alignment of the amino acid sequence of the EHV-1 TK with the TKs from 3 other herpesviruses revealed regions of homology, some of which correspond to the previously identified substrate binding sites, while others have as yet, no assigned function. In particular, the strict conservation of an aspartate within the proposed nucleoside binding site suggests a role in ATP binding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 55 publications
(45 reference statements)
2
41
1
Order By: Relevance
“…4. Coalignment of the putative nucleotide-(a) and nucleoside-(b) binding sites of the predicted amino acid sequences of the TKs of EHV-4, EHV-1 (Robertson & Whalley, 1988), PRV (Kit, 1985a, b), BHV-I (Mittal & Field, 1989), BHV-2 (Sheppard & May, 1989), MarHV (Otsuka & Kit, 1984), HSV-1 (Wagner et al, 1981), HSV-2 (Kit et aL, 1983), VZV (Davison & Scott, 1986), EBV (Baer et al, 1984), HVS (Honess et al, 1989), MDV (Scott et al, 1989) and HVT (Scott et al, 1989). Residues conserved in all 13 herpesviruses are indicated below each alignment in upper case lettering.…”
Section: Xhoimentioning
confidence: 99%
See 3 more Smart Citations
“…4. Coalignment of the putative nucleotide-(a) and nucleoside-(b) binding sites of the predicted amino acid sequences of the TKs of EHV-4, EHV-1 (Robertson & Whalley, 1988), PRV (Kit, 1985a, b), BHV-I (Mittal & Field, 1989), BHV-2 (Sheppard & May, 1989), MarHV (Otsuka & Kit, 1984), HSV-1 (Wagner et al, 1981), HSV-2 (Kit et aL, 1983), VZV (Davison & Scott, 1986), EBV (Baer et al, 1984), HVS (Honess et al, 1989), MDV (Scott et al, 1989) and HVT (Scott et al, 1989). Residues conserved in all 13 herpesviruses are indicated below each alignment in upper case lettering.…”
Section: Xhoimentioning
confidence: 99%
“…The nucleotide sequences of the TK genes of a variety of herpesviruses, including EHV-1, have been reported (reviewed in Robertson & Whalley, 1988;Honess et al, 1989;Mittal & Field, 1989;Scott et aL, 1989). Here we report the nucleotide sequence of the EHV-4 TK gene and compare selected regions of the predicted amino acid sequence of its protein to those of other herpesvirus TK proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore it is possible that the process of virus penetration is either a multi-step event or can proceed by independent mechanisms. For EHV-1, genes homologous to gB and gH have been sequenced (Robertson & Whalley, 1988;Whalley et al, 1989), and the products of these genes identified (Meredith et al, 1989;Bonass et al, 1990;L. A. Taylor, unpublished results).…”
Section: Discussionmentioning
confidence: 99%